Development and Maturation of Embryonic Cortical Neurons Grafted into the Damaged Adult Motor Cortex - Ballout, Nissrine; Frappé, Isabelle; Péron, Sophie; Jaber, Mohamed; Zibara, Kazem; Gaillard, Afsaneh (Frontiers in Neural Circuits, 2016)
Injury to the human central nervous system can lead to devastating consequences due to its poor ability to self-repair. Neural transplantation aimed at replacing lost neurons and restore functional circuitry has proven to be a promising therapeutical avenue. We previously reported in adult rodent animal models with cortical lesions that grafted fetal cortical neurons could effectively re-establish specific patterns of projections and synapses. The current study was designed to provide a detailed characterization of the spatio-temporal in vivo development of fetal cortical transplanted cells within the lesioned adult motor cortex and their corresponding axonal projections. We show here that as early as two weeks after grafting, cortical neuroblasts transplanted into damaged adult motor cortex developed appropriate projections to cortical and subcortical targets. Grafted cells initially exhibited characteristics of immature neurons, which then differentiated into mature neurons with appropriate cortical phenotypes where most were glutamatergic and few were GABAergic. All cortical subtypes identified with the specific markers CTIP2, Cux1, FOXP2 and Tbr1 were generated after grafting as evidenced with BrdU co-labeling. The set of data provided here is of interest as it sets biological standards for future studies aimed at replacing fetal cells with embryonic stem cells as a source of cortical neurons.